Performance evaluation based fault tolerant control with actuator saturation avoidance - Boussaid, Boumedyen; Aubrun, Christophe; Abdelkrim, Mohamed Naceur; Ben Gayed, Mohamed Koni (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a new approach regarding a reconfigured system is proposed to improve the performance of an active fault tolerant control system. The system performance is evaluated with an intelligent index of performance. The reconfiguration mechanism is based on a model predictive controller and reference trajectory management techniques. When an actuator fault occurs in the system, a new degraded reference trajectory is generated and the controller calculates new admissible controls. A constraint set and cost function are established to avoid actuator saturation and reduce the control energy spent in closed loop dynamics. The effectiveness of the proposed method is illustrated using a hydrothermal system subject to actuator faults and constraints on actuator dynamic ranges.
Keywords: fault tolerant control systems; performance degradation; reference management; model predictive control; performance index